Unsustainable Fiscal Policies in the EU, A Legacy of the 1970s? - Vieira, Carlos (2004)
The recent controversy over the excessive deficit procedure in Germany and France has reopened the discussion over the long run sustainability of fiscal policies. This paper tests the hypothesis of stainability in a group of six EU countries, with an econometric methodology allowing the consideration of often lected structural breaks in the data. It is found that, prior to EMU, only Germany followed a ustainable fiscal policy, ensuring a bounded debt-GDP ratio. The negative shock to government finances of the early 1970s appears to be still affecting the European economies.